Differences in Neuropathogenesis of Encephalitic California Serogroup Viruses - Evans, Alyssa B.; Winkler, Clayton W.; Peterson, Karin E. (Emerging infectious diseases, 2019)
The California serogroup of orthobunyaviruses comprises a group of mosquitoborne viruses, including La Crosse (LACV), snowshoe hare (SSHV), Tahyna (TAHV), Jamestown Canyon (JCV), and Inkoo (INKV) viruses, that cause neurologic disease in humans of differing ages with varying incidences. To determine how the pathogenesis of these viruses differs, we compared their ability to induce disease in mice and replicate and induce cell death in vitro. In mice, LACV, TAHV, and SSHV induced neurologic disease after intraperitoneal and intranasal inoculation, and JCV induced disease only after intranasal inoculation. INKV rarely induced disease, which correlated with less viral antigen in the brain than the other viruses. In vitro, all viruses replicated to high titers; however, LACV, SSHV, and TAHV induced high cell death, whereas JCV and INKV did not. Results demonstrated that CSG viruses differ in neuropathogenesis in vitro and in vivo, which correlates with the differences in pathogenesis reported in humans.